Subject Scheduling Application Using Genetic Algorithm - Wijaya, Benny; Irawadi, Syafrul; Sari, Lili Indah; Probonegoro, Wishnu Aribowo (IJISTECH (International Journal of Information System and Technology), 2023)
Scheduling is a very important issue in an educational institution. The many obstacles sometimes make scheduling difficult to create. One method for solving such problems is to use genetic algorithms. Based on this background, the formulation of the problem of this study is "how to implement genetic algorithms for subject scheduling applications at SMK Bakti Pangkalpinang". The purpose of this study is to implement genetic algorithms for subject scheduling, formulate subject scheduling problems so that they can be solved with genetic algorithms and help schedule preparation to be more efficient. Genetic algorithms are heuristic search algorithms based on biological evolutionary mechanisms. In this study the author uses a prototype model, which includes activities such as gathering needs, designing and evaluating. The result of this study is an application that can be used to compile a lesson schedule with the desired results. Testing is done with blackbox testing and the test results show the application can function properly.